The Optimal Digestible Leucine-to-Lysine Ratio in Wheat-Based Diets for Finishing Broilers - Diana Siebert; Christian Scharch (Animals)
Male Ross 308 finisher (19 to 33 days) broiler chickens (n = 672) were used to determine the standardized ileal digestible (SID) leucine (Leu)-to-lysine (Lys) ratio for the maximum growth performance and slaughter parameters. A basal diet (incl. wheat, triticale, soybean meal, sunflower meal, and synthetic amino acids) deficient in Leu was formulated, and supplementary L-Leu was used to achieve 0.9 and 1.25 SID Leu-to-Lys ratios in increments of 0.05. A slight deficiency in lysine was implemented to truly relate broiler performance to changes in the SID Leu-to-Lys ratio. Diets were fed to broilers in seven pens (12 broilers each). Eight birds per pen were used for carcass evaluation on day 33. Data analysis indicated that SID Leu-to-Lys ratios between 0.96 and 1.025 were required to achieve 95% and 98% of the maximum body weight gain, daily feed consumption, and the European production efficacy factor, respectively. The estimation of recommended SID Leu-to-Lys ratios for the feed conversion ratio and carcass parameters was not possible.